2022
DOI: 10.1017/s1047951122001081
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of salivary cortisol levels to reflect stress response in children undergoing congenital heart surgery

Abstract: Aim: This study aimed to provide baseline information on the potential role of salivary cortisol in reflecting the stress response in children undergoing congenital heart surgery. Patients and methods: Children underwent congenital cardiac surgery, aged between one and seventeen years were included. Saliva samples were collected pre- and postoperatively by the health caregiver immediately after the children woke up (07:00–09:00 am) and at 06:00 pm in the evening. Salivary cortisol levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
6
2
Order By: Relevance
“…Studies on the association of children with (surgically corrected) CHD and cortisol levels are rare and inconsistent. One study found differences from normal reference values regarding the diurnal variability of salivary cortisol levels in children with CHD [ 58 ], while Stonawski et al [ 51 ]—based on our own data—found no differences in diurnal cortisol release between the VSD and control group at primary school age. In adolescence, instead of salivary cortisol, which rather measures acute cortisol production and is sensitive to diurnal rhythm [ 59 ], hair cortisol values were used to enable the investigation of cumulative distress over a one-month time period [ 60 ].…”
Section: Aims Of This Studycontrasting
confidence: 53%
“…Studies on the association of children with (surgically corrected) CHD and cortisol levels are rare and inconsistent. One study found differences from normal reference values regarding the diurnal variability of salivary cortisol levels in children with CHD [ 58 ], while Stonawski et al [ 51 ]—based on our own data—found no differences in diurnal cortisol release between the VSD and control group at primary school age. In adolescence, instead of salivary cortisol, which rather measures acute cortisol production and is sensitive to diurnal rhythm [ 59 ], hair cortisol values were used to enable the investigation of cumulative distress over a one-month time period [ 60 ].…”
Section: Aims Of This Studycontrasting
confidence: 53%
“…43,44 Indeed, studies in infants and young children with cCHD have demonstrated that altered stress markers, measured by serum and salivary cortisol, are associated with complications during the ICU stay such as prolonged mechanical ventilation and inotrope medication and with the cardiopulmonary bypass surgery. [5][6][7] In our cohort, we found no significant association between stress markers in hair at ages 10 to 15 years and length of ICU stay following open heart surgery in infancy and other clinical variables.…”
Section: Altered Stress Markers In Early Adolescents With Cchdcontrasting
confidence: 66%
“…Several studies have suggested that high early life stress may alter the function of the HPA axis and consequently alter stress markers such as cortisol and cortisone . Indeed, studies in infants and young children with cCHD have demonstrated that altered stress markers, measured by serum and salivary cortisol, are associated with complications during the ICU stay such as prolonged mechanical ventilation and inotrope medication and with the cardiopulmonary bypass surgery …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with other published works on the matter and may explains why the determination of a clear cutoff value of cortisol levels as a surrogate biomarker for stress is notoriously elusive in the literature. A recent study on child undergoing congenital cardiac surgery have found that salivary cortisol levels can be considered a predictive indicator of anxiety on pre- and postoperative period ( 25 ) .…”
Section: Discussionmentioning
confidence: 99%